2020
DOI: 10.1038/s41416-020-0820-z
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic value of 18F-FDG-PET to predict the tumour immune status defined by tumoural PD-L1 and CD8+tumour-infiltrating lymphocytes in oral squamous cell carcinoma

Abstract: BACKGROUND: Lately, immune checkpoint proteins, such as programmed death 1 (PD-1) and its ligand-1 (PD-L1), have garnered attention as a new target in oral squamous cell carcinoma (OSCC). Reportedly, fluoro-D-glucose (FDG)-uptake alteration by anti-PD-1 antibody treatment depicts the response in patients with lung cancer. This study aims to elucidate the correlations between tumour immune status, clinicopathological factors, 18 F-FDG-uptake and cold tumour phenotypes as low PD-L1 expression/low CD8 + tumour-in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 49 publications
0
30
0
1
Order By: Relevance
“…Furthermore, adipocytes are associated with systemic hypoxia and cancer progression in the tumor microenvironment (TME) 34 . Several studies demonstrated that HIF-1A/GLUT1 signaling is related to 18 F-FDG uptake among patients with cancer and metabolic disorder 18 , 35 . Moreover, glucose metabolism in tumor cells has been reported to play crucial roles in tumor progression by regulating local tumor immunity 36 .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, adipocytes are associated with systemic hypoxia and cancer progression in the tumor microenvironment (TME) 34 . Several studies demonstrated that HIF-1A/GLUT1 signaling is related to 18 F-FDG uptake among patients with cancer and metabolic disorder 18 , 35 . Moreover, glucose metabolism in tumor cells has been reported to play crucial roles in tumor progression by regulating local tumor immunity 36 .…”
Section: Discussionmentioning
confidence: 99%
“…However, the most commonly used detection methods such as flow cytometry for blood samples and immunohistochemistry for tissue biopsy fail to provide comprehensive and dynamic information and have certain limitations. Moreover, it is challenging for 18 F-FDG to distinguish between pseudoprogression and immune-related adverse events [ 22 , 23 ]. ImmunoPET will provide great help for precisely stratifying patients into responders and nonresponders before treatment, and determining to continue or terminate therapy during the process or even predicting the patient outcome by tracking CD8 + T cells.…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies have investigated the complex relationship between tumor immune microenvironment and glucose metabolism rate and shown associations between metabolic and immune profiles [ 15 , 16 ]. 2-[ 18 F]FDG PET imaging has been suggested as a diagnostic tool to estimate tumor immune status [ 17 ]. Our hypothesis was that higher mutational load (as reflected by TMB) might correlate with metabolic reconfiguration [ 18 ], and immune inflammatory response [ 12 ], and that either of these features would be associated with a higher SUV max [ 19 ].…”
Section: Discussionmentioning
confidence: 99%